2003
DOI: 10.1034/j.1600-0528.2003.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

A 5‐year evaluation of two glass‐ionomer cements used as fissure sealants

Abstract: Sealing pits and fissures with glass-ionomer cements was effective in preventing caries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 29 publications
0
30
0
8
Order By: Relevance
“…In contrast, other studies have indicated that, for the permanent teeth of children and adolescents, resinbased sealants are more effective than GIC at reducing caries at 24 to 44 months after implementation [11][12][13][14] . Thus, there is conflicting evidence as to whether GIC may reduce the prevalence of caries in children's permanent teeth 9,12,[15][16][17] . When molars are in an eruption process, moisture control is not possible.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other studies have indicated that, for the permanent teeth of children and adolescents, resinbased sealants are more effective than GIC at reducing caries at 24 to 44 months after implementation [11][12][13][14] . Thus, there is conflicting evidence as to whether GIC may reduce the prevalence of caries in children's permanent teeth 9,12,[15][16][17] . When molars are in an eruption process, moisture control is not possible.…”
Section: Introductionmentioning
confidence: 99%
“…As far as protection against secondary caries is concerned, no significant differences were observed between materials. A low retention index was obtained for Ketac GIC and Vitremer RMGIC after five years (57). The total retention index was less than 2% (1.6%) for both materials.…”
Section: Development Of Sealing Methods and Applied Materialsmentioning
confidence: 84%
“…Clinical studies showed low retention index for GICs used as sealants in observation periods from six months to seven years (73). Although a high percentage of sealant loss was observed , it was not directly related to development of caries (25,57,74,76). Examples of such sealants were: ASPA, Fuji III, Ketac Cem, Ketac Bond, Chemfil Superior.…”
Section: Development Of Sealing Methods and Applied Materialsmentioning
confidence: 99%
“…The first permanent molars were cleaned with a pumice slurry in Robinson brushes, washed, etched with 37% phosphoric acid (15 seconds), washed (15 seconds) and air-dried. Under isolation with cotton rolls, the material was applied as follows 17 …”
Section: Resin-modified Glass Ionomer Cement Application On the Occlumentioning
confidence: 99%